Strategic Flexibility and its Impact on Raising the Performance of Banks - Hayder Jerri Mohsin; Jawad Al-Frijawy; Ahmed Talib Hameed; Laith Yousef Bani Hani; Noor Aldeen Kassem Al-Alawnh (Journal of Social Commerce, 2022)
Strategic issues are the core of the work of business organizations and occupy the main pillar of the work of commercial banks, whose fields of work and their competitive environment have developed. Strategic flexibility has become an urgent and binding issue for the commercial banking sector to keep pace with environmental changes and developments and raise the performance of banks to keep pace with environmental developments. The research aims to delve into two very important variables by doing The commercial banking sector, which is flexibility   The strategy and performance of the banks. Six commercial banks were chosen to be happy with the research (Baghdad, Iraqi investment, Gulf, investment development, Al-Mansour, Babylon). A member of bank managers, people's officials, and accountants in commercial banks. The data were subjected to statistical analysis by applying the statistical program (spss). The results demonstrated an impact on the overall level of the two variables. The study (strategic flexibility, bank performance) The findings revealed the existence of relationships between (banking service flexibility, competitive flexibility, investment flexibility, and human resource flexibility). And bank performance at the sub-dimension level (financial dimension, customer dimension, internal operations dimension, education and growth dimension). The study came to a set of conclusions and suggestions.